2000
DOI: 10.1177/102490790000700102
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Management North of the Shenzhen River

Abstract: A study was carried out in a district hospital located close to the Hong Kong-Shenzhen border, in order to get a picture of the epidemiology of diseases and injuries sustained by Hong Kong residents in China. The emergency medical treatment provided and the degree of patient satisfaction were also analysed. The majority of the patients were adult males. Trauma constituted more than 50% of the attendance, with traffic accident and common assault being the leading causes. This group of Hong Kong residents prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Patients who suffered from perforation were significantly older, more frequently had co-morbidities, and were more likely to have delayed surgery. These findings are consistent with observations of other studies showing that older patients present with more advanced forms of appendicitis [7,9,[13][14][15][16][17][18]22]. The logistic regression showed that age was the most important factor influencing the perforation rate, followed by co-morbidity and delay.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Patients who suffered from perforation were significantly older, more frequently had co-morbidities, and were more likely to have delayed surgery. These findings are consistent with observations of other studies showing that older patients present with more advanced forms of appendicitis [7,9,[13][14][15][16][17][18]22]. The logistic regression showed that age was the most important factor influencing the perforation rate, followed by co-morbidity and delay.…”
Section: Discussionsupporting
confidence: 91%
“…The influence of age on perforation rate has been addressed in a number of studies. One of the major reasons might be delay to diagnosis, as elderly patients wait longer to seek medical care [7,17,22,26]. Another possible reason might be emergency department wait times.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations